Evaluation Of Interest Rate Free In Indonesian Islamic Banking - Roikhan Mochamad Aziz; Syahrul Syahrul (Universitas Muhammadiyah Mataram, 2018)
The purpose of this study reviewed the analysis and discussion in a thesis entitled